Press Councils in Portugal and France : something new on the Western front - Fidalgo, Joaquim (2009)
In a time when ultra-liberalism, de-regulation and market-driven trends increasingly dominate the media business, but also when their ‘clients’ increasingly demand to have a more active voice in the public communication process, the issues of media responsibility and media accountability seem to be gaining a renewed interest. The technological environment of our digital era, with the expansion of Internet, of social networks and of opportunities for selfedition, allowed many new actors to enter the media field, or to get much closer to it, claiming for a new relationship between the traditional media ‘producers’ and the traditional media ‘consumers’. These last ones demand more and more to be regarded as citizens, rather than just ‘consumers’, and therefore as partners in the process of news production and diffusion in the public sphere. But in order to achieve this, media must also be willing to open the doors of their ‘fortresses’ and accept that transparency and interaction with their publics are an unavoidable prerequisite for the legitimization of their power in a democratic society. This is what media social responsibility is all about, after all. In this context, an important role could be played by the so-called Media Accountability Systems (M*A*S*, as they were named by Claude-Jean Bertrand), and particularly by the Press Councils – mechanisms that bring together representatives of the media industry, of the journalists and of the public, in order to held the media more accountable on a voluntary, self-regulated basis. In the last year, two movements emerged in two Western European countries, both trying to launch a Press Council: France (where such a mechanism never existed, although the country was a pioneer in the struggle for press freedom) and Portugal (where a Press Council was created in 1975, soon after the recovery of democracy, but was extinguished fifteen years later, having been somehow replaced by a State-driven regulatory entity). In spite of their obvious differences, these two cases, besides coinciding in time, show some similarities that deserve our attention and can be regarded as examples of new trends in the media landscape. It is our purpose, in this paper, to look at the French and the Portuguese cases, trying to understand their specific backgrounds and to systematize the arguments of the main protagonists of the two movements going on. We’ll do this, in a first moment, through historical and documental research, and, in a second moment, through interviews to some of the leading supporters of this idea in both countries. As for the Portuguese case, we’ll also evoke the experience of the former Press Council, trying to shed light on the (mostly political) motives that led to its premature death.